The Relationship Between Mother’s Knowledge, Attitudes, and Eating Behavior with Toddler Nutritional Status (W/H) in the Sulamadaha Health Center - Asriyanti Sagaf; Suryani Mansyur; Diah Merdekawati Surasno (BIOSAINSTEK, 2026)
Sulamadaha Health Center ranked third in the highest wasting cases in Ternate City in 2024. The factor that plays an important role in meeting the nutritional needs of toddlers is the maternal factor. This study aims to determine the relationship between maternal knowledge, attitudes, and eating behavior with the nutritional status of toddlers based on the W/H (Weight/ height) indicator in the Sulamadaha Health Center Working Area of Ternate City. This study is a quantitative research. The population in this study were all mothers who have toddlers in the Sulamadaha Health Center. A sample of 240 respondents was taken. Data on maternal Knowledge, Attitudes, and Behavior were obtained through interviews using a questionnaire, while data on Toddler Nutritional Status were measured through anthropometric measurements, namely measuring height or length and also body weight. Data were analyzed univariately and bivariately using the Pearson chi-square test. (α = 0.05). The nutritional status of toddlers using the W/H indicator consists of the categories of wasting 48 respondents (20%), normal 160 respondents (68.3%), and overweight 28 respondents (11.7%). The statistical test results showed a significant relationship between maternal knowledge (p value= 0.04), maternal attitudes (p value= 0.000), and eating behavior with toddler nutritional status (p value = 0.041). It is recommended that the Sulamadaha Health Center increase nutritional counseling for mothers of toddlers and provide assistance to families experiencing malnutrition. It is also recommended that mothers of toddlers be proactive in increasing their knowledge and behavior in implementing healthy eating patterns for their families.